LASERPUNCTURE TECHNOLOGY AS AN EFFORT PREPARATION OF SIAM CATFISH SEED (Pangasianodon hypophthalmus) MASS - Patmadevi, Maulia; Ahmad Taufiq Mukti; Ahmad Shofy Mubarak; Suryani Dyah Astuti (Jurnal Biosains Pascasarjana, 2024)
The spawning of striped catfish which is very dependent on the season and environmental conditions results in the unavailability of mature gonad broodstock during the dry season. The alternative that is often done is by biological stimulation using the ovaprim hormone and laserpuncture technology. The purpose of this study was to determine the effect of giving the ovaprim hormone, laserpuncture induction and a combination of the two on the speed of spawning time and the fecundity value of Striped catfish. This study used an experimental method with a completely randomized design with 3 treatments and 6 replications. The results of this study were the average spawning time for broodstock treated with laserpuncture and ovaprim hormone and the fecundity value was significantly different from the other treatments (p<0.05). Based on the results of the study, it can be concluded that the combination of 0.5 ml/kg of ovaprim hormone and laser puncture at a dose of 0.5 J/cm2 for 32.66 seconds can speed up the spawning time and fecundity of striped catfish.